Dual Pharmacological Targeting of HDACs and PDE5 Inhibits Liver Disease Progression in a Mouse Model of Biliary Inflammation and Fibrosis - Claveria-Cabello, Alex (Cancers (Basel), 2020)
SIMPLE SUMMARY: Chronic liver injury and inflammation leads to excessive deposition of extracellular matrix, known as liver fibrosis, and the distortion of the hepatic parenchyma. Liver fibrosis may progress to cirrhosis, a condition in which hepatic function is impaired and most cases of liver tumors occur. Currently, there are no effective therapies to inhibit and reverse the progression of liver fibrosis, and therefore, chronic liver disease remains a global health problem. In this study we have tested the efficacy of a new class of molecules that simultaneously target two molecular pathways known to be involved in the pathogenesis of hepatic fibrosis. In a clinically relevant mouse model of liver injury and inflammation we show that the combined inhibition of histones deacetylases and the cyclic guanosine monophosphate (cGMP) phosphodiesterase phosphodiesterase 5 (PDE5) results in potent anti-inflammatory and anti-fibrotic effects. Our findings open new avenues for the treatment of liver fibrosis and therefore, the prevention of hepatic carcinogenesis. ABSTRACT: Liver fibrosis, a common hallmark of chronic liver disease (CLD), is characterized by the accumulation of extracellular matrix secreted by activated hepatic fibroblasts and stellate cells (HSC). Fibrogenesis involves multiple cellular and molecular processes and is intimately linked to chronic hepatic inflammation. Importantly, it has been shown to promote the loss of liver function and liver carcinogenesis. No effective therapies for liver fibrosis are currently available. We examined the anti-fibrogenic potential of a new drug (CM414) that simultaneously inhibits histone deacetylases (HDACs), more precisely HDAC1, 2, and 3 (Class I) and HDAC6 (Class II) and stimulates the cyclic guanosine monophosphate (cGMP)-protein kinase G (PKG) pathway activity through phosphodiesterase 5 (PDE5) inhibition, two mechanisms independently involved in liver fibrosis. To this end, we treated Mdr2-KO mice, a clinically relevant model of liver inflammation and fibrosis, with our dual HDAC/PDE5 inhibitor CM414. We observed a decrease in the expression of fibrogenic markers and collagen deposition, together with a marked reduction in inflammation. No signs of hepatic or systemic toxicity were recorded. Mechanistic studies in cultured human HSC and cholangiocytes (LX2 and H69 cell lines, respectively) demonstrated that CM414 inhibited pro-fibrogenic and inflammatory responses, including those triggered by transforming growth factor β (TGFβ). Our study supports the notion that simultaneous targeting of pro-inflammatory and fibrogenic mechanisms controlled by HDACs and PDE5 with a single molecule, such as CM414, can be a new disease-modifying strategy.